2019
DOI: 10.1002/ajcp.12300
|View full text |Cite
|
Sign up to set email alerts
|

Positive School Climate as a Moderator of Violence Exposure for Colombian Adolescents

Abstract: Highlights• Community violence witnessing and victimization are associated with externalizing behaviors.• Armed conflict exposure is associated with externalizing behaviors and developmental competence.• School safety, connectedness, and services moderate relation between witnessing and externalizing.• School services moderates relation between victimization and competence.• School climate has implications for mitigating the effects of violence exposure for adolescents.Abstract In Colombia, many adolescents ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 73 publications
3
29
0
10
Order By: Relevance
“…Ozer et al () noted that in addition to the understudied nature of schools as a moderator for community violence exposure, findings to date have been mixed. A recent study of school climate as a moderator of violence exposure in Colombian youth found while three dimensions of school climate moderated the effects of witnessing community violence on externalizing behavior, none of them moderated the effects of witnessing community violence on developmental competence, and only one of those dimensions moderated the effects of victimization in the community on developmental competence (Galas, Lindstrom Johnson, White, Pettigrew, & Dumka, ).…”
Section: Introductionmentioning
confidence: 99%
“…Ozer et al () noted that in addition to the understudied nature of schools as a moderator for community violence exposure, findings to date have been mixed. A recent study of school climate as a moderator of violence exposure in Colombian youth found while three dimensions of school climate moderated the effects of witnessing community violence on externalizing behavior, none of them moderated the effects of witnessing community violence on developmental competence, and only one of those dimensions moderated the effects of victimization in the community on developmental competence (Galas, Lindstrom Johnson, White, Pettigrew, & Dumka, ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, community violence can affect the school environment, which can negatively influence students and teachers' well-being. For that, it is important to build school environments with the conditions to moderate or compensate for the negative effects that violence can have on individuals and communities, as Gaias et al (2019) point out. Even in risky environments with high rates of violence, something can be done to diminish the negative impact of violence in individuals.…”
Section: Discussionmentioning
confidence: 99%
“…But not only a positive school climate serves to prevent school violence, it could also work as a protective factor against the negative effects of being exposed to different types of community violence. A recent study from Gaias et al (2019) that used a sample of 1857 Colombian adolescentes, showed from that some aspects of school environment can protect students from the detrimental implications that violence can have on their development.…”
Section: School Climatementioning
confidence: 99%
“…Un mecanismo de influencia de los pares sobre la aparición y mantención de la conducta antisocial es por medio de las normas de grupo. Se ha estudiado que, dentro de los grupos de pares, los niveles de tolerancia y aceptación hacia las conductas de violencia o agresión pueden explicar su desarrollo y mantención (Benbenishty, Astor, Zeira & Vinokur, 2002;Caicedo & Jones, 2014;Gaias, Lindstrom, White, Pettigrew & Dumka, 2019). Considerando esto, Vitaro et al (2015) observaron, en una muestra de 266 pares de gemelos de Montreal, Canadá, la existencia de factores genéticos comunes que influirían en la conducta antisocial y, a su vez, que podría ser moderada por las normas de grupo, evidenciando la importancia de los pares en estas conductas.…”
Section: Conductas Antisociales E Influencia De Los Paresunclassified
“…Para comprender mejor la influencia del espacio escolar sobre el desarrollo psicosocial de los estudiantes, es importante considerar, también, que los objetivos de la escuela como institución formadora ya no se reducen solo a la entrega de información por medio de procesos unidireccionales de interacción, sino que incluyen la responsabilidad de los actores educativos de promover procesos de desarrollo integral en los estudiantes (Casassus, 2002). De esta forma, se reconoce que aquellos contextos escolares que son capaces de satisfacer las necesidades sociales y emocionales de sus estudiantes permiten una mayor probabilidad de aprendizaje de los contenidos curriculares, junto a la generación de una mayor motivación por aprender y un aumento del compromiso con la escuela, reduciendo, de esta manera, deserciones, repitencias y expulsiones en la trayectoria escolar (Bruns et al, 2016;Catalano, Haggerty, Oesterle, Fleming & Hawkins, 2004;Gaias et al, 2019;Hawkins, Catalano, Kosterman, Abbott & Hill, 1999;Jimmerson, Nickerson, Mayer & Furlong, 2012;Johnson, Crosnoe & Elder Jr., 2001;Malecki & Elliot, 2002).…”
Section: La Escuela Como Factor Protector De Conductas Antisociales Yunclassified